Sustainable Public Management and Institutional Social Responsibility in Practice: A Study of Four Challenges in the Polish Context - Nesterak, Janusz (Journal of Public Governance, 2024)
Contemporary public management – both at the local level and at the institutional level – requires a fundamental transformation. The complexity of today’s social, economic, and environmental challenges calls for a governance model grounded in integration, sustainability, and active civic participation. Only such an approach can foster institutions capable of acting effectively under the conditions of uncertainty while remaining committed to the principles of social justice, inclusiveness, and long-term accountability.